Effect of Surfactants on Thermal Conductivity of Graphene Based Hybrid Nanofluid - W.X. Hong, N.A.C. Sidik, R. Saidur (International Journal of Advanced Science and Technology, 2020)
Varioushybridnanofluidshavebeenresearchedinthisdecade.Thequalityofthissaid-to-be alternate heat transfer medium depends on two major features – long term stability and high thermal conductivity. In recent years, graphene-based nanofluid was reported to exhibit distinguished heat transfer performance compared to most materials investigated in past studies. This study aims to compare the effect of different surfactants on thermal conductivity of graphene-based nanofluid. Sodium dodecyl benzenesulfonate (SDBS) and hexadecyltrimethyl ammonium bromide (CTAB) were mixed separately in advance with the mixture of water and ethylene glycol. Total 0.025 to 0.1 wt% of nanoparticles were added into the mixture of base fluid and surfactant followed by ultrasonication. Mono nanofluid was produced by adding graphene nanoplatelets (GnP) only whereas a novel hybrid combination was composed of graphene nano platelets and titanium dioxide. Stability of each sample was inspected using zeta potential analysis and Uv-vis spectroscopy. Thermal conductivity of samples from 30 oC to 60 oC was measured using Decagon KD2 Pro. Both surfactants contributed to high zeta potentialvalueandminimalsedimentationforallnanofluids.CTABimprovedthethermalconductivity of hybrid nano fluid more compared to SDBS, with 11.72% difference at 0.1 wt% nano particles concentration when compared to base fluid at 60 oC. The highest enhancement (23.74%) on base fluid was spotted at 60 oC, where 0.1 wt% of GnP was mixed with CTAB. Surprisingly, both surfactants had minimal impact on viscosity and density when compared to effect of nanoparticles. These findings could strengthen literatureonsuitablesurfactanttobeusedongraphenebasednanofluidsincelimitedcomparisonwork has be end one. High thermal conductivity of the hybridnano fluidat high temperature could be used as coolant in cooling system.